The City’s Social Portrait: An Interview with Petr Georgievich Shchedrovitsky - Shchedrovitsky, Petr; Grigoryeva, Elena; Mayarenkov, Sergey (project baikal, 2018)
The interview with the president of the G. P. Shchedrovitsky Institute for Development Petr Shchedrovitsky was held by the architect Elena Grigoryeva and the member of the Board of the Siberian Laboratory of Urbanistics Sergey Mayarenkov and touched upon the strategies of urban development. The participants discussed the unevenness in the economic and social development, the conditions of formation of new social groups, the dependence of managing the family budget on cultural values, as well as the case studies of different cities.
Keywords: economics; proletariat; precariat; bourgeoisie; city; efficiency of the labour system; family budget; public spaces